Psychosocial barriers to promoting self-directed and autonomous learning: The perception of students and lecturers in Malaysia - Esmaeil, Ahmad Azmi Abdel Hamid; Dzulkifli, Dg Norizah Binti Ag Kiflee @; Maakip, Ismail; Halik, Murnizam; Marshall, Sanen (Journal of Education and e-Learning Research, 2024)
It can be difficult to align with the present theoretical change in education from teacher-centered to student-centered learning especially in high-power distance cultures like Malaysia that are communal. This study aims to investigate the perceptions of students and lecturers regarding the psychosocial barriers to promoting self-directed and autonomous learning in the Malaysian context. The qualitative research method was chosen based on the research questions. Qualitative research allows the researcher to understand people’s beliefs, attitudes, perceptions and behaviors. This study used purposive sampling and semi-structured interviews were conducted with thirteen students and four lecturers at a Malaysian public university. The study found two types of challenges: personal (within the student) and environmental (surrounding the student). Personal obstacles include ideas about the value of education such as an emphasis on grades and diplomas as well as attitudes towards life, such as a propensity for hedonism and a need for spoon-feeding. Environmental barriers include a lack of encouragement for critical thinking, the development of student dependency, issues with university regulations, family and lecturers’ attitudes and teaching methods. These challenges were explained using Hofstede’s, self-determination and ARCS theories. The study highlights how important it is for teachers to modify their pedagogical approaches and attitudes in order to encourage student-centered learning as well as how important it is for students to get more assistance and support.